Haemophagocytic lymphohistiocytosis (HLH) in adult with dengue infection - Wong, KCS; Ahmad Khaldun Ismail; Wan Mohd Shukri WNA; Cheah SK (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Haemophagocytic lymphohistiocytosis (HLH) or haemophagocytic syndrome is a rare but life-threatening syndrome of excessive immune activation with nonspecificclinical presentation. HLH is one of the complications in dengue infection. A 69-year-old lady was treated for severe dengue with multi-organ dysfunction with superimposed pneumonia, requiring mechanical ventilation. However, persistent cytopenia despite blood transfusion without evidence of haemorrhage raised the suspicion of HLH. Further blood investigations revealed hypertriglyceridaemia, hypofibrinogenaemia and hyperferritinaemia. Bone marrow aspiration showed haemophagocytosis. Patient fulfilled the diagnostic criteria for HLH by HLH-2004 trial. Her HScore is 281, with the probability of having HLH is 99.9%. Patient’s condition improved after administration of intravenous immunoglobulin (IVIG) and intravenous dexamethasone in tapering doses. Early specific treatment of HLH with IVIG and/or corticosteroid is important but diagnosis is usually delayed due to nonspecific clinical findings and laboratory results. High index of suspicion with the aid of diagnostic criteria by HLH-2004 trial and HScore is helpful to recognise this syndrome.